PENGARUH READ ALOUD DALAM MENGEMBANGKAN BAHASA PADA ANAK DI RAUDHATUL ATHFAL AR-RAHMAN KINALI: THE EFFECT OF READ ALOUD IN DEVELOPING LANGUAGE FOR CHILDREN AT RAUDHATUL ATHFAL AR-RAHMAN KINALI - BAITI LATIFA; ANNISA FITRIA; DELFI ELIZA (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
Children's language development still experiences difficulties in expressing the child's ability to understand the performance of receptive language skills and expressive language skills. One reason is because the stimulus given by the teacher in learning at Raudhatul Athfal Ar Rahman Kinali is less varied both in terms of strategies, methods and learning media used. The purpose of this study was to determine the effect of reading aloud in developing language in children at Raudhatul Athfal Ar Rahman Kinali. The research method used is a qualitative research method with a descriptive approach. The research subjects in this study were students of Raudhatul Athfal Ar Rahman Kinali who were group B, and in this study the subjects studied totaled 15 students. Data collection techniques are observation, interview, and documentation techniques. The results showed that reading aloud has an effect on developing language in children in Raudhatul Athfal Ar Rahman Kinali with the benefits obtained after doing this activity is to increase children's interest in reading activities, increase vocabulary mastered by children, children are able to retell the contents of stories they have heard with own language.